2015
DOI: 10.1111/ans.13273
|View full text |Cite
|
Sign up to set email alerts
|

Dual nerve transfer of gracilis and adductor longus nerves in restoration of complete femoral nerve palsy

Abstract: Isolated permanent femoral nerve palsy is a rare pathology that causes significant disability. 1,2 A true unilateral complete proximal femoral nerve palsy will result in the wasting of the quadriceps, iliacus and sartorius, variable wasting of pectineus and a sensory deficit in the anteromedial thigh and medial aspect of the leg. This causes a well-described gait disturbance and renders the patient unable to ambulate independently without significant difficulty or the use of gait aids. 3 The aetiology of isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…12 It remains unclear which muscle or nerve transfers are suitable to replace enough quadriceps function to achieve this end point. Improvement in knee extension function has been achieved via neurorrhaphy of the anterior branch of the obturator nerve to femoral nerve branches 6,11 ; however, the literature seems to support augmenting the nerve transfer with a second nerve transfer or nerve grafting to achieve improved function. Nguyen et al 5 reports that, in patients with a tumor resection resulting in loss of quadriceps muscles, training and physiotherapy after gracilis muscle transfer allow patients to achieve unassisted ambulation, normal to near-normal-appearing gait, and full or nearly full knee joint extension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 It remains unclear which muscle or nerve transfers are suitable to replace enough quadriceps function to achieve this end point. Improvement in knee extension function has been achieved via neurorrhaphy of the anterior branch of the obturator nerve to femoral nerve branches 6,11 ; however, the literature seems to support augmenting the nerve transfer with a second nerve transfer or nerve grafting to achieve improved function. Nguyen et al 5 reports that, in patients with a tumor resection resulting in loss of quadriceps muscles, training and physiotherapy after gracilis muscle transfer allow patients to achieve unassisted ambulation, normal to near-normal-appearing gait, and full or nearly full knee joint extension.…”
Section: Discussionmentioning
confidence: 99%
“…6,[8][9][10] A case of a dual nerve transfer in which the obturator nerve branches to the gracilis and adductor longus muscles are transferred into the vastus intermedius nerve branch and vastus medialis nerve branch has also been reported. 11 Tung et al 6 reported 2 cases of obturator nerve transfer for complete femoral nerve injury. One patient had incomplete femoral nerve recovery after the nerve transfer, which resulted in an inability to climb stairs, whereas the second patient's reconstruction was augmented with a superior gluteal nerve transfer, which resulted in improved function.…”
mentioning
confidence: 99%
“…Even with novel descriptions of anatomical anomalies and anatomical variation found on imaging and intraoperatively, the main innovations appear to be in how this is clinically applied. For example, Karagiannis and Ferris 17 use of collateral nerve supply to inform the selection of the gracilis and adductor longus nerves in repairing a femoral nerve palsy reflects the innovative use of anatomical function and partial redundancy. Such an understanding and appreciation of normal anatomical arrangements and the potential flexibility afforded that can be exploited to restore function is just one example of a case study to inspire students of anatomy and demonstrate that discipline of clinical surgical anatomy is alive and kicking.…”
Section: Discussionmentioning
confidence: 99%
“…While some patients were reported to have improved sensory and motor function recovery, this study was limited by its design, and further studies are needed to confirm the benefits of ES [51] . Notably, one concern with implantable neuroprosthesis is an induced foreign body reaction, which can compromise benefits by provoking an inflammatory response [52] . However, systemic dexamethasone treatment for 2 weeks in rats was found to significantly attenuate the inflammatory response, demonstrating a potential adjuvant therapy to improve the function of neuroprostheses [52] .…”
Section: Electrical Stimulationmentioning
confidence: 99%
“…Notably, one concern with implantable neuroprosthesis is an induced foreign body reaction, which can compromise benefits by provoking an inflammatory response [52] . However, systemic dexamethasone treatment for 2 weeks in rats was found to significantly attenuate the inflammatory response, demonstrating a potential adjuvant therapy to improve the function of neuroprostheses [52] .…”
Section: Electrical Stimulationmentioning
confidence: 99%